Experimental Study on the Mining-Induced Water-Resistance Properties of Clay Aquicludes and Water Conservation Mining Practices - Zhenli Fan; Kesong Fan; Zhiguo Liu; Yutong Feng; Hua Wei; Yunsen Zhou (Advances in Civil Engineering)
The Yushen mining area contains thin bedrock and a shallow buried coal seam, where JingLe group Hipparion clay and Lishi loess serve as a high-quality cement insulation cover. This study investigates the properties of the clay layer to determine the effect of the clay aquiclude on the mining water variation and fracture characteristics. Unloading hydraulic jack experiments were performed to test the physical and mechanical properties of the clay layer and the structure was analyzed in detail. The experimental results show that mining affects the soil cracks, leading to crack opening and subsequent bridging. The permeability coefficient of the soil layer initially increases with increased unloading and then decreases. A theoretical model is developed to determine the recovery mechanism of the clay layer water insulation based on the spatial movement of the clay. The results indicate the formation of a waterproof cover type of coal mud protection. Design methods are proposed to optimize the coal pillar size. Mining damage leads to the formation of a mud-covered bridge belt, which can be designed to appropriately reduce the protective layer thickness. The model is applied to the Hao Jialiang 2301 working face. The results provide important insight on the variation characteristics of the mining water insulation in clay layers and an important reference for accurately calculating the size parameters of waterproof protective coal pillars under mud-cap conditions to increase the upper mining limit of the working face.